PRINCESSES WHO ACTIVELY PARTICIPATED IN GOVERNMENT (Universal International Scientific Journal, 2026)
This article covers the lives and activities of the queens who lived and worked during the Timurid dynasty and the Babur dynasty, who actively participated in the governance of the state in historical processes. In particular, it discusses the entry into the political arena and the role they played in governance of queens such as Saraymulk Khanum, Shodimulk Begum, Jahonaro Begum, and Qabaj Khotun.
Keywords: Timurid queens, court ladies, Shodimulk Beg, Gavharshod Beg, Mohlaroyim, Nodirayi era, women in social life, medieval queens.